Factors associated with dental visit and barriers to utilisation of oral health care services in a sample of antenatal mothers in Hospital Universiti Sains Malaysia - Saddki, Norkhafizah; Yusoff, Azizah; Hwang, Yew L (BioMed Central, 2010)
Background: The aims of this study were to determine factors associated with dental visit and to describe barriers to utilisation of oral health care services among antenatal mothers attending the Obstetric and Gynaecology Specialist clinic in Hospital Universiti Sains Malaysia. Methods: A structured, self-administered questionnaire was used obtain information on the variables of interest pertaining to the current pregnancy from 124 antenatal mothers. Results: The majority of the mothers claimed that their oral health status was good (67.0%) or very good (2.4%). On the contrary, most of them admitted of having had at least one oral health problem (59.7%) including cavitated (43.5%) and painful teeth (15.3%), bleeding gum (21.0%), and bad breath (10.5%). However, only 29% of the mothers visited dentist during the current pregnancy. Factors associated with the mothers’ dental visit were exposure to oral health education before the pregnancy and awareness of relationship between poor maternal oral health and adverse pregnancy outcomes with odds ratio of 4.06 (95% CI: 1.67-9.78) and 3.57 (95% CI: 1.30-9.77) respectively. Common excuses given by most mothers include perceptions of not having any oral health problems (65.9%), long waiting time at the clinic (71.6%), and no immediate treatment given by the dentist (64.8%). Conclusions: Utilisation of oral health care services among antenatal mothers was low. Mothers who reported dental visit were more likely to be those who had received oral health education before the current pregnancy and knew of the association between poor maternal oral health and adverse pregnancy outcomes. Dissatisfaction with the services rendered and perceptions of not having any oral health problems were the main barriers.